The Effectiveness of Using the Zoom Meeting Application in Improving Learning during the Covid-19 Pandemic - Yudi Supiyanto; Ganda Agustina Hartati Simbolon; Tamsik Udin; Ida Bagus Benny Surya Adi Pramana (Budapest International Research and Critics University, 2022)
This study aims to determine the effectiveness of using the zoom meeting application in improving learning during the pandemic. The method used in this research is as follows: qualitative research methods. Qualitative research as according to Creswell, that qualitative research is defined as an approach that aims to explore, and understand a dynamic. In addition, the data collection technique is through a list of questions distributed via the WhatsApp application. The result of this research is that the benefits of Information and Communication Technology (Zoom Meeting) have only been implemented during this Social Distancing era, thus requiring the lecture process to be conducted online. Lectures carried out using Zoom Meeting are considered less effective because they are often constrained by the availability of network/internet signals for students who do not use wifi and will have an impact on the quality of ongoing learning. The advantages of using Zoom Meetings are considered practical and efficient for students because by using Zoom Meetings, communication between students and lecturers is easier than communicating in writing or via short messages practical for students. Therefore, with the existence of the Zoom Meeting application, it is hoped that it can support students in terms of online-based learning and it is hoped that students can use this application as effectively as possible. Therefore, students and lecturers must understand each other in distance learning during the Covid-19 pandemic. We must accept the dynamics in the Covid-19 pandemic era because this phenomenon is a step and encouragement for every university in utilizing technology-based learning and is also a step towards the industrial revolution 4.0. Changes in distance learning that are carried out in the form of online lectures, of course require time to be able to adapt lectures to the current situation because lectures are in online form, requires the availability of supporting instruments to support the continuity of the online learning process.